2006
DOI: 10.1002/eji.200535111
|View full text |Cite
|
Sign up to set email alerts
|

IL‐7Rα expression on CD4+ T lymphocytes decreases with HIV disease progression and inversely correlates with immune activation

Abstract: Many factors can influence the rate of HIV disease progression, including those that maintain T cell homeostasis. One key homeostatic regulator is the IL‐7 receptor (IL‐7R). Previous studies have shown IL‐7R expression levels decrease in HIV infection, but effects on memory subtypes, CD4+ T cells, and cell function have not been explored. The present study examined the expression of the IL‐7Rα chain on naïve and memory T lymphocyte subsets of both HIV‐positive and HIV‐negative individuals from Nairobi, Kenya t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
80
1
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 53 publications
13
80
1
3
Order By: Relevance
“…For example, although Bcl-2 was found to be expressed in peripheral T-lymphocytes and strongly correlated with spontaneous T cell apoptosis [32][33][34][35], in lymph nodes, Bcl-2 was detected primarily in the B (mantle zone of the germinal centers) and not in the T cell area. Similarly, IL-7Ra was found to be expressed on peripheral T and B cells, and peripheral CD4+ T cell depletion correlated well with the down-regulation of IL-7Ra [36,37]. In lymph nodes, IL-7Ra which increased after therapy was detectable only in the germinal centers and not in the T cell area.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, although Bcl-2 was found to be expressed in peripheral T-lymphocytes and strongly correlated with spontaneous T cell apoptosis [32][33][34][35], in lymph nodes, Bcl-2 was detected primarily in the B (mantle zone of the germinal centers) and not in the T cell area. Similarly, IL-7Ra was found to be expressed on peripheral T and B cells, and peripheral CD4+ T cell depletion correlated well with the down-regulation of IL-7Ra [36,37]. In lymph nodes, IL-7Ra which increased after therapy was detectable only in the germinal centers and not in the T cell area.…”
Section: Discussionmentioning
confidence: 82%
“…In lymph nodes, IL-7Ra which increased after therapy was detectable only in the germinal centers and not in the T cell area. The absence of IL-7Ra expression in the T cell area resembles those peripheral T cells in which a strong association of decreased IL-7Ra expression with low Bcl-2 expression has been found [36,37]. In lymph nodes, a significant down-regulation of TRAIL was found after therapy due primarily to the reduction of cells of the phagocytic type, whereas TRAIL was not identifiable in B or T lymphocytes.…”
Section: Discussionmentioning
confidence: 83%
“…Third, immune activation (largely measured as increased expression of CD38 þ and HLA-DR þ on T-cells) has also been shown to be inversely correlated with IL-7Ra expression on CD4 T-cells in HIV-infected patients, 45,46 and immune activation has a negative impact on CD4 T-cell recovery. [47][48][49] Although we did not compare the immune activation levels in the UARTO and Caucasian patients, numerous studies have described a higher degree of immune activation both in HIVuninfected [50][51][52][53][54] and HIV-infected African patients [53][54][55][56] as compared with patients from high-income countries owing to differences in the environment 52 and prevalence of other co-infections.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In HIV infection, we and others have demonstrated that CD127 is expressed on a lower proportion of CD4 + and CD8 + T cells compared to that observed in HIV-uninfected individuals. 2,4 Interleukin (IL)-7 activity is important for T cell development, homeostasis, memory development, and T cell effector functions. Despite the increase in IL-7 in HIV disease, 5 cytolytic T cell activity (CTL) becomes impaired with disease progression.…”
mentioning
confidence: 88%
“…1 Impaired CD4 + and CD8 + T cell function and decreased CD127 expression have recently been linked to abnormal activation of the immune system in HIV + individuals and resulting immunodeficiency. 2 Expression of CD127 on both naive and memory CD8 + and CD4 + T cells has recently been shown to be inversely correlated with CD8 + T cell exhaustion in the context of persistent exposure to antigen 2 and the expansion of effector CD8 + T cells during chronic HIV infection. 8 The cellular mechanism linking antigen persistence to decreased CD127 expression is not known.…”
mentioning
confidence: 99%